Edukasi Cara Minum Obat Maag yang Benar (Antasida, Ranitidine & Omeprazole) pada Pasien Rawat Jalan Puskesmas Rawat Inap Cempaka - Samsul Hadi; Indryani Syarifuddin; Kunti Nastiti; Pertiwi Awilda; Sheila Nurrahmah; Siti rahimah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Dyspepsia (ulcer) is a collection of upper gastrointestinal symptoms including pain or discomfort in the gastro-duodenal area (epigastrium/tenati), burning, fullness, fullness, nausea or vomiting. The purpose of this health education activity is to increase the knowledge and understanding of the community, especially in the Inpatient Health Center environment regarding dyspepsia including signs and symptoms, how to use drugs, and prevention. The activity includes several stages, namely material presentation using lecture method and leaflet media, question and answer session, pretest, and post test. The percentage results of the average pretest value are 37.30% and the average post test is 67.70%. The conclusion of this study is that there is an increase in community knowledge in Puskesma Rawat Inap Cempaka after being given education and exposure to dyspepsia material.